2013
DOI: 10.1002/ajp.22163
|View full text |Cite
|
Sign up to set email alerts
|

Chimpanzee nesting patterns in savanna habitat: Environmental influences and preferences

Abstract: Data on chimpanzee (Pan troglodytes) nesting patterns were collected in Issa, Ugalla, western Tanzania. Ugalla is one of the driest, most open, and seasonal habitats inhabited by chimpanzees. We investigated the physical characteristics of nests and trees used for nesting to understand environmental influences on nest building and identify the characteristics preferred by the chimpanzees and the basis for such preferences. We analyzed 2,167 nests and 1,523 nesting trees. Most nests were built in the middle sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
71
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(82 citation statements)
references
References 59 publications
9
71
1
1
Order By: Relevance
“…The selection of nesting site, nest height and nest-bearing trees by chimpanzees described by several authors [Basabose and Yamagiwa, 2002;Furnichi and Hashimoto, 2004; and O 'Malley, 2008;Koops et al, 2012;Hernandez-Aguilar et al, 2013;Ndiaye et al, 2013b;Hakizimana et al, 2015] are also illustrated in the nesting behaviour of chimpanzees in Diaguiri. In this area, chimpanzees most often nested in woodland and grassland with isolated trees, while in Assirik, within the NKNP, chimpanzees nested less frequently in these habitats [Pruetz et al, 2008].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The selection of nesting site, nest height and nest-bearing trees by chimpanzees described by several authors [Basabose and Yamagiwa, 2002;Furnichi and Hashimoto, 2004; and O 'Malley, 2008;Koops et al, 2012;Hernandez-Aguilar et al, 2013;Ndiaye et al, 2013b;Hakizimana et al, 2015] are also illustrated in the nesting behaviour of chimpanzees in Diaguiri. In this area, chimpanzees most often nested in woodland and grassland with isolated trees, while in Assirik, within the NKNP, chimpanzees nested less frequently in these habitats [Pruetz et al, 2008].…”
Section: Discussionmentioning
confidence: 96%
“…Although no single characteristic has been found sufficient for explaining preferences in terms of nest tree species, nest tree selectivity has been linked generally to physical characteristics of the trees [Furnichi and Hashimoto, 2004;Hernandez-Aguilar, 2006;Ndimuligo, 2007;Stanford and O'Malley, 2008;Koops et al, 2012;Hernandez-Aguilar et al, 2013;Carvalho, 2014]. In light of the tremendous variation in nesting tree characteristics, managers of natural resources need to take account of information on nesting tree preference by chimpanzee populations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The deep ancestry of this trait has possible implications for our understanding of the cognitive evolution of early hominoids [1], as it permits higher-quality sleep by providing thermoregulation [2], [3], reduced vulnerability to predators [2], [4], [5], more comfortable sleeping postures [4], [6], [7], and protection against pathogens [2], [4], [8]. The impact of environmental factors on the location of great ape nests has been the subject of a number of studies [6], [9]–[18], and nest counts are frequently used to estimate ape population density [19][29]. However the functionality of great ape nesting sites in relation to the dynamics of their social organization has been much less well-documented [1].…”
Section: Introductionmentioning
confidence: 99%
“…At Fongoli, 3% of the nests were located on the ground [Pruetz et al, 2008], and when this site was compared to Assirik, it was concluded that nest height was related to presence or absence of large carnivores that may prey on the chimpanzees, as most predators had been exterminated at the Fongoli site. With no predators in the captive environment, this may be another explanation for Chimp Haven's chimpanzees nesting most often on the ground [McGrew, 2004;Stewart et al, 2011;Hernandez-Aguilar et al, 2013].…”
Section: Discussionmentioning
confidence: 99%